Delayed greening during leaf expansion under ambient and elevated CO2 in tropical tree seedlings. (10th December 2021) - Vogado, Nara O.; Cheesman, Alexander W.; Cernusak, Lucas A.
Abstract: Tropical tree species employ varying strategies in young leaves to minimise losses to herbivory. The young leaves of species with delayed greening are thought to be less visible to herbivores, but likely incur a cost to leaf‐level carbon gain via lower photosynthetic rates during leaf development. Increasing atmospheric CO2 concentrations may reduce the cost of delayed greening, and/or modify leaf expansion rates, altering the ecological interaction of species. In this study, we evaluated the effects of elevated CO2 concentrations on physiological responses of three Australian rainforest tree species, two with delayed greening in young leaves. Net photosynthesis rates were significantly lower in recently flushed leaves of species with delayed greening than in the species with normal greening. Yet, surprisingly, total nitrogen concentrations were higher in the former than in the latter. Intrinsic water‐use efficiency increased at a steeper rate during leaf development under elevated CO2 in all three species, irrespective of greening strategy. Leaf growth rate, in terms of area expansion, did not increase under elevated CO2 in any of the species. Although elevated CO2 did not boost the performance of the delayed greening species more than that of the normal greening species, we found higher nitrogen concentrations in their young leaves. This supports the intriguing possibility that delayed greening may have evolved in these species to protect young leaves that are especially rich in nitrogen.